PENERAPAN MODEL ADVANCE ORGANIZER PADA PEMBELAJARAN SENI TARI DI SMA NEGERI 3 PARIAMAN - Zulfika Putri; Fuji Astuti; Herlinda Mansyur (FBS Universitas Negeri Padang, 2018)
Abstract This research aimed to describe the implementation of Advance Organizer model on Dance subject at SMA 3 Pariaman.This research was qualitative research using descriptive method. The object of the research was 30 students of XI grade of SMA 3 Pariaman, The research instrument was the researcher herself and additional instruments were observation sheet and test. The data were attained through library research, observation, documentation, performance test. Then, the data were analyzed. The results of this study indicated that the implementation of Advance Organizer learning model in Dance subject with material to identify the type, role, and development of paired dance / group of archipelago at SMA 3 Pariaman with 3 meeting ran well. Students are motivated and interested in learning. This can be seen from the cognitive improvements and students’ learning activities at each meeting with indicators: paying attention to teacher’s explanation, doing question and answer, expressing opinions, the spirit of learning, and being able to conclude the lesson. At the meeting I, II, and III, it was seen the development of learning in the cognitive domain of students. From the lack of responses from students until students become more active and the cognitive of students in the lesson rose. Improvement can also be seen from the achievement of dance learning objectives. Thus it can be concluded that the application of Advance Organizer model in Dance subject were very effective in improving the students' cognitive knowledge, and mad the learning atmosphere become more fun so that it can increase students’ activity. With the increase of students’ learning activities, it will increase in knowledge along with it and appear on students’ learning outcomes at SMA 3 Pariaman.Kata Kunci: Model Advance Organizer, Seni Tari